2005
DOI: 10.1007/s10826-005-1115-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Witnessing Violence, Peer Provocation, Family Support, and Parenting Practices in the Aggressive Behavior of Rural Adolescents

Abstract: This study examined the influence of witnessing violence, peer provocation, family support, and parenting practices (monitoring and discipline) on aggression. Participants were 1,196 ninth graders at nine schools in poor, predominantly agricultural, rural communities who completed measures of these variables. Witnessing violence, peer provocation, low levels of family support, and poor parenting practices were each related to higher frequencies of aggression. Witnessing violence and peer provocation partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 39 publications
7
40
0
2
Order By: Relevance
“…Otras investigaciones han puesto de manifiesto que el excesivo tanto control conductual como psicológico o, las prácticas educativas caracterizadas por ausencia de control, también favorecen la aparición de conductas de agresividad en los hijos (Krnutson, DeGarmo y Reid, 2004;Mazefsky y Farell, 2005).…”
Section: Prácticas Educativas Paternas Y Agresividad En Estudiantes Uunclassified
See 1 more Smart Citation
“…Otras investigaciones han puesto de manifiesto que el excesivo tanto control conductual como psicológico o, las prácticas educativas caracterizadas por ausencia de control, también favorecen la aparición de conductas de agresividad en los hijos (Krnutson, DeGarmo y Reid, 2004;Mazefsky y Farell, 2005).…”
Section: Prácticas Educativas Paternas Y Agresividad En Estudiantes Uunclassified
“…Así, diversas investigaciones han evidenciado que el control conductual, caracterizado por la exigencia de responsabilidades, el establecimiento de límites y la supervisión, se relaciona negativamente con la aparición de agresividad en los hijos. Sin embargo, cuando los padres utilizan métodos basados en el control psicológico, como es la inducción de culpa o el chantaje emocional, los hijos tienden a manifestar en mayor medida comportamientos violentos (Márquez, Villarreal, Verdugo y Montes, 2014).Otras investigaciones han puesto de manifiesto que el excesivo tanto control conductual como psicológico o, las prácticas educativas caracterizadas por ausencia de control, también favorecen la aparición de conductas de agresividad en los hijos (Krnutson, DeGarmo y Reid, 2004;Mazefsky y Farell, 2005).Un aspecto relacionado con el control por parte de los padres y que cabe mencionar, es el conocimiento que éstos tienen de distintos aspectos de la vida de sus hijos. En este sentido Kerr y Stattin (2000) indican que en ocasiones, la forma de determinar el control parental ha consistido en evaInternational Journal of Developmental and Educational Psychology…”
unclassified
“…Other studies have shown that characteristics related to cultural and familial interdependency are protective against smoking for late adolescent African American girls (Nasim, Corona, Belgrave, Utsey, & Fallah, 2006). For example, ethnic and racial socialization have been found to moderate the relationship between psychobehavioral risks and tobacco and other substance use behaviors (Belgrave, Brome, & Hampton, 2000;Brook & Pahl, 2005;Burlew et al, 2000;Nasim, Belgrave, Jagers, Wilson, & Owens, in press); family structure and relationship quality have been found to mediate negative neighborhood risks for substance use (Mazefsky & Farrell, 2005); and religiosity (e.g., importance, internal, external) has been found to buffer against substance use (Nasim, Utsey, Corona, & Belgrave, 2006;Oler, 1996). However, little attention has been afforded to protective factors against community risks and substance use for rural African American.…”
Section: Protective Factors For Community Disorganization and Substanmentioning
confidence: 99%
“…For example, children who report poor parenting experience more peer provocation and a greater likelihood of becoming a victim of physical assault from others, which in turn magnifies their aggression (Mazefsky & Farrell, 2005). Even the poor parental monitoring that can lead to witnessing community violence may contribute to child aggression, since it establishes a social context that provides perfect conditions for observational learning and internalizing the conviction that aggression is widely acceptable.…”
Section: Introductionmentioning
confidence: 99%